Aggregate shape and tensile strength measurement - De Freitas Seben Jr., Getulio [UNESP]; Corá, José Eduardo [UNESP]; Fernandes, Carolina [UNESP]; Lal, Rattan (Wolters Kluwer, 2013)
Tensile strength (TS) of soil aggregates is an important indicator of soil quality. However, TS varies with aggregate shape. Thus, the objective of this study was to quantify the influence of aggregate shape on TS and propose a shape standardization protocol to increase accuracy in the measurement of TS. The latter was determined on 7,560 aggregates divided into three shapes, (i) irregular shape (IS), (ii) spherical shape (SS), and (iii) flat surface (FS), while preserving the inherent structure of the aggregate. The aggregates with IS had a larger range in the TS (306 kPa) because of the shape variability when compared with SS (238 kPa) and FS (129 kPa). The TS determined in aggregates with FS had smaller coefficient of variation (46%) in comparison with those of IS (70%) and SS (66%), indicating that the aggregate uniformity reduced the influence of shape on the TS. A smaller force (42.12 kPa) was needed to rupture aggregates with FS than IS (58.43 kPa) and SS (56.89 kPa) because of better force distribution in causing the tensile stress. The use of aggregates with the FS enables an accurate assessment of TS in relation to a wide range of management treatments. Copyright © 2013 by Lippincott Williams & Wilkins.
Keywords: aggregate rupture; aggregation; Oxisol; soil friability; soil strength; Structural properties of soil